IMPLEMENTASI STRATEGI SOCIAL MEDIA MARKETING DALAM MENINGKATKAN LOYALITAS PELANGGAN PADA UMKM - Tri Hajjah Sari (MANAJEMEN, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a sector that plays an important role in the national economy, especially in creating jobs and driving local economic growth. In Medan City, MSMEs are growing rapidly but also face major challenges in maintaining customer loyalty amidst tight digital competition. This study aims to analyze the implementation of social media marketing strategies in increasing customer loyalty among MSME actors in Medan City, North Sumatra. Using a descriptive qualitative approach, data was collected through in-depth interviews with several MSME actors and local business observers. The results of the study show that effective social media strategies, such as the use of creative content, personalized messages, and two-way interactions, can build emotional relationships with customers and increase their loyalty to the brand. In addition, customer engagement through platforms such as Instagram and TikTok has been shown to strengthen trust and increase the likelihood of repeat purchases. This study concludes that social media marketing is an important strategy in maintaining and expanding the MSME customer base. Therefore, it is necessary to improve digital understanding and sustainable content strategies so that MSMEs can compete effectively in the digital era.